Laparoscopic Total Fundoplication for Refractory GERD: How to Achieve Optimal Long-Term Outcomes by Preoperative Instrumental Assessment and a Standardized Technique - Limongelli, Paolo; Tolone, Salvatore; Genio, Gianmattia del; d’Alessandro, Antonio; Rossetti, Gianluca; Brusciano, Luigi; Docimo, Giovanni; Ruggiero, Roberto; Gili, Simona; Topatino, Assia; Amoroso, Vincenzo; Casalino, Giuseppina; et al. (IntechOpen, 2012)
None